Becoming Solar: Towards More-Than-Human Understandings of Solar Energy - Angela Mackey; Monserrat Vallejo de la Guarda; Oscar Tomico; Ron Wakkary; Troy Nachtigall; Martijn de Waal (Temes de Disseny, 2023)
In this article we examine the experiences of the first and second author who have changed themselves to become newly attuned to the sun, or who have “become solar”. Motivated by calls to approach solar design in novel, less technocratic ways, we reflect on their one-year journey to gain a new relationship with solar energy as an explicitly more-than-human design (MTHD) approach. We argue that their perception of solar energy progressively worked to decentre them as human actors in this new solar-energy arrangement, revealing other nonhuman actors at play, instigating situations of care and attention to those nonhumans and ultimately guiding them towards what it means to be solar. For solar design, we see this approach as creating a new lens for solar designers to draw from. For MTHD, we see this acting as a practical example for designers seeking to begin transforming themselves in their own practice by taking initial steps towards a MTHD approach.